EIB Working Paper 2021/02 - The birth of new high growth enterprises internationalisation through new digital technologies - Pál, Rozália (European Investment Bank, 2021)
Internationalisation and the adoption of new digital technologies play an important role in the formation of new high growth enterprises. This paper examines this relationship for high growth enterprises in Europe and the UK, using data from the EIB Investment Survey and ORBIS. Its results highlight the complex influence of exporting and foreign direct investment on the capacity to become a high growth enterprise and the role of new digital technologies in this process.